Addressing the emerging threat of Oropouche virus: implications and public health responses for healthcare systems - Olalekan John Okesanya; Blessing Olawumi Amisu; Olaniyi Abideen Adigun; Mohamed Mustaf Ahmed; Abdulmajeed Opeyemi Agboola; Tolga Kab; Gilbert Eshun; Bonaventure Michael Ukoaka; Tolutope Adebimpe Oso; Jerico Bautista Ogaya; Don Eliseo Lucero-Prisno (Tropical Diseases, Travel Medicine and Vaccines, 2025)
Abstract Oropouche fever is an increasingly significant health concern in tropical and subtropical areas of South and Central America, and is primarily spread by midge vectors. The Oropouche virus (OROV) was first identified in 1955 and has been responsible for numerous outbreaks, particularly in urban environments. Despite its prevalence, the disease is often under-reported, making it difficult to fully understand its impact. OROV typically causes febrile illness characterized by symptoms such as headaches, muscle pain, and, occasionally, neurological issues such as meningitis. The ability of the virus to thrive in both forested and urban areas has raised concerns regarding its potential spread to new regions, particularly in the context of climate change. This paper delves into the epidemiology, clinical features, and transmission patterns of OROV, shedding light on the difficulties in diagnosing and managing the disease. The absence of specific treatments and vaccines highlights the urgent need for continued research and development of targeted public health strategies. Advancements in molecular diagnostics and vector control strategies can mitigate Oropouche fever’s impact. However, a comprehensive public health approach involving increased surveillance, public education, and cross-border collaboration is needed, especially as the global climate crisis may expand vector habitats, posing risks to previously unaffected regions.